(untitled) (Research, Society and Development, 2022)
Medicinal plants have been considered a solution to public health problems. The World Health Organization (WHO) emphasizes that up to 80% of the population of developing countries trust Complementary or Alternative Medicine (CAM) in initial health care. Thus, the research aims to describe the importance of using herbal medicines as an alternative and complementary treatment in primary care. The present study is an integrative literature review with descriptive content and qualitative nature. Data for this study were obtained from the following databases: Virtual Health Library (BVS), Scielo, Lilacs, medline and from the Academic Google directory. Original studies available and fully published that addressed the guiding question, between the years 2000 and 2020, were considered; in Portuguese, English or Spanish. Results: Aiming at greater safety and greater control in the use of herbal medicines, ANVISA (National Health Surveillance Agency) has several resolutions that regulate the procurement, quality and distribution (sale) of herbal medicines. The Ministry of Health (MS) provides the use of 12 herbal medicines in the public health network and these drugs are directly related to the treatment of diseases in primary care such as: mild to moderate hypercholesterolemia, burns, inflammation, infections, occasional constipation, bronchospasm and bronchoconstriction. Several studies prove the benefits of herbal medicines, especially in a complementary way for promoting and restoring the health of the population.